Experientially relevant borders and new categories of identity - Furu, Adél (Balcanica Posnaniensia. Acta et studia, 2025)
The present paper aims to provide an analysis of the effect of the border, the social practices related to it and their consequences on the ethnic and national identification and categorization mechanisms that exist within the two biggest communities living in Transylvania. The paper examines the manners of crossing the border in any direction in the case of the Hungarian and Romanian speakers residing in Transylvania, inquires into the distinction and separation procedures as regards the existing borders and into the cultural consequences of travelling across the border. We use the following research questions to develop this study: What kind of identity categories appear when crossing the border? What types of transnational discourses of power are evoked that may qualify the Romanian speakers at the border crossing? What is the message that reaches the Hungarian speakers during the border crossing experiences? Can we identify any hybridization in the border zone of Transylvania?